2021
DOI: 10.1002/emp2.12463
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric internal carotid artery dissection and stroke after minor head injury

Abstract: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…In adult stroke patients, abundant randomized clinical trials have produced robust evidence to support well-established guidelines for management; this is not the case in the pediatric population [66]. Standardized treatment recommendations are limited by a lack of evidence, and the latest guidelines from the 2008 American Heart Association (AHA) and American Stroke association management guidelines for children suggest intravenous anticoagulation for 3 to 6 months bridged to oral anticoagulation in patients with extracranial dissection; furthermore, treatment with anticoagulation is not recommended for intracranial dissections [56].…”
Section: Presentation Symptomatology and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult stroke patients, abundant randomized clinical trials have produced robust evidence to support well-established guidelines for management; this is not the case in the pediatric population [66]. Standardized treatment recommendations are limited by a lack of evidence, and the latest guidelines from the 2008 American Heart Association (AHA) and American Stroke association management guidelines for children suggest intravenous anticoagulation for 3 to 6 months bridged to oral anticoagulation in patients with extracranial dissection; furthermore, treatment with anticoagulation is not recommended for intracranial dissections [56].…”
Section: Presentation Symptomatology and Managementmentioning
confidence: 99%
“…Further studies are needed. The AHA has also suggested that the decision to use thrombectomy in children can follow adult parameters; however, to date, no thrombectomy trials have included individuals under the age of 18 [66]. Therefore, the role of endovascular therapy and its true benefits are unclear [66].…”
Section: Presentation Symptomatology and Managementmentioning
confidence: 99%